The Effect of Low-Dose Dexmedetomidine on Perioperative Neurocognitive Dysfunction in Elderly Patients Undergoing Endoscopic Retrograde Cholangiopancreatography (ERCP): A Randomized, Controlled, Double-Blind Trial - Sun Z; Shi J; Liu C; Zhang J; Liu Y; Wu Y; Han X; Dai H; Wu J; Bo L; Wang F (Dove Medical Press, 2024)
Zhangnan Sun,1,* Ji Shi,2,* Chaolei Liu,1 Jingjing Zhang,1 Yue Liu,1 Yini Wu,3 Xin Han,3 Hong Dai,3 Jimin Wu,3 Lijun Bo,1 Faxing Wang3 1Department of Anesthesiology, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, People's Republic of China; 2Department of Anesthesiology, The First Hospital of Hebei Medical University, Shijiazhuang, Hebei, People's Republic of China; 3Department of Anesthesiology, Lishui People's Hospital, Lishui Hospital of Wenzhou Medical University, Lishui, People's Republic of China*These authors contributed equally to this workCorrespondence: Faxing Wang, Department of Anesthesiology, Lishui People's Hospital, Lishui Hospital of Wenzhou Medical University, No. 15, Dazhong Street, Lishui, Zhejiang Province, 323000, People's Republic of China, Email wfx2023@wmu.edu.cn Lijun Bo, Department of Anesthesiology, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050000, People's Republic of China, Email 27901566@hebmu.edu.cnObjective: This study investigates the effect of low-dose dexmedetomidine infusion on perioperative neurocognitive function in elderly patients undergoing endoscopic retrograde cholangiopancreatography (ERCP).Patients and Methods: This double-blind trial enrolled 80 elderly ERCP patients randomized to receive dexmedetomidine (Group D) or placebo (Group S). Group D received dexmedetomidine at 0.4 μg·kg− 1·h− 1 starting 15 minutes before surgery until completion, along with propofol at 1.5 mg/kg for anesthesia. Group S received saline and propofol in a similar manner. Anesthesia was maintained with dexmedetomidine at 0.4 μg·kg− 1·h− 1 and propofol at 1- 2 mg/kg during surgery. Cognitive function was assessed using the Mini-Mental State Examination (MMSE) preoperatively and on postoperative days 1, 3, and 5. Primary outcome was perioperative neurocognitive disorder (PND) incidence on day 5; secondary outcomes included changes in perioperative IL-6, cortisol, S100-β, hemodynamics, anesthesia parameters, postoperative pain, agitation scores, and adverse events.Results: All 80 patients completed the trial. On postoperative day 5, the cumulative probability of PND incidence was significantly lower in Group D than in Group S (12.5% vs 35%, P=0.018). Group D also had lower levels of IL-6 (F=199.472, P< 0.001), S100-β (F=2681.964, P< 0.001), and cortisol (F=137.637, P< 0.001). Propofol doses were lower in Group D (706.1 ± 202.4 vs 1003.3 ± 203.7, P< 0.001), and bradycardia rates were higher (45% vs 15%, P=0.003), though atropine use did not significantly differ between groups. Group D showed greater stability in mean arterial pressure. Postoperative complications and adverse reactions were similar across groups.Conclusion: Perioperative low-dose dexmedetomidine infusion with propofol in elderly ERCP patients ensures safe and effective monitored anesthesia care (MAC), reducing PND incidence by mitigating peripheral inflammation and stress responses. Long-term follow-up is needed to fully evaluate PND incidence.Keywords: ERCP, PND, dexmedetomidine, elderly patients